Double-blind Randomized Evaluation of Intercostal Nerve Blocks as an Adjuvant to Subarachnoid Administered Morphine for Post-thoracotomy Analgesia. Issue 5 (September 1995) - Liu, Maywin; Rock, Peter; Grass, Jeffrey A.; Heitmiller, Richard F.; Parker, Stephen J.; Sakima, Neal T.; Webb, Michael D.; Gorman, Randolph B.; Beattie, Charles
Abstract : Background and Objectives: Thoracotomy is associated with pain and compromised pulmonary function. Intercostal nerve blocks (INB) and subarachnoid morphine (SM) act on different portions of the pain pathway. Each is effective for post-thoracotomy pain relief. The combination of these two modalities in relieving post-thoracotomy pain and improving postoperative pulmonary function has not been investigated. Methods: In a double-blind study, 20 patients undergoing lateral thoracotomy for lung resection were randomized to receive 0.5 mg SM preoperatively and INB with bupivacaine (INB+) prior to wound closure or 0.5 mg SM with INB using saline (INB-). Visual analog scale pain scores at rest, with cough, and with movement of the ipsilateral arm, forced expiratory volume in 1 second (FEV1 ), and forced vital capacity (FVC) were measured at 4, 24, 48, and 72 hours after the operation. Opioid use was measured during the initial 24 hours after the operation. Results: At 4 hours, the INB+ group demonstrated better FEV1 (56.6% vs. 40.4% of baseline, P < .05) and FVC values (54.6% vs. 39.6% of baseline, P < .05) and less resting and cough pain ( P < .05). However, FEV1 continued to decline in the INB+ group at 24 hours to lower than the INB- group although pain scores were similar beyond 4 hours. Opioid usage during the first 24 hours was similar (INB-, 16.7 mg vs. INB+, 13.2 mg, P = .7). Conclusions: Although postoperative INB provided modest improvements in pain and pulmonary function when used as an adjuvant to 0.5 mg SM for post-thoracotomy analgesia, the benefits were transient. The authors do not recommend adding INB for patients undergoing lateral thoracotomy who receive 0.5 mg SM.